"Lubuskie Nadodrze" (2000-2003) - ambitna próba reaktywacji pisma kulturalno-społecznego = "Lubuskie Nadodrze" (2000-2003) - an ambitious attempt to reactivate the cultural and social journal - Wojewódzki, Ireneusz (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The monthly "Lubuskie Nadodrze" was a social and cultural magazine published in Zielona Góra in the years 2000-2003. It was intended to be a continuation of the bi-weekly "Nadodrze" published between 1957-1990. The article shows the history of the emergence of this monthly magazine and the cause of its decline in 2003. It was issued by the Zielona Góra Culture Center, and financed from the budget of the city of Zielona Góra. After the local government elections in 2002, the new city authorities took away the grant for the magazine. This political decision, resulting from the perception of the magazine as politically engaged for the left-wing, influenced its fate. The article also brings together the content of the monthly magazine which gave voice to many talented and young authors and had a chance to reach the rank of an important publication.
Keywords: czasopisma; Lubuskie Nadodrze (czasopismo); Zielonogórski Ośrodek Kultury; magazines